Du capsien chasseur au capsien pasteur Pour un modèle régional de néolithisation - Belhouchet, Lotfi (Archaeopress Publishing, 2022)
Du capsien chasseur au capsien pasteur draws on recent fieldwork to put forward a model for neolithisation in the Eastern Maghreb. The analysis of occupation habits is essential for an understanding of ancient societies. In the Eastern Maghreb, studies on the Capsian culture have been considerably enriched in recent years, but have not yet been properly synthesised to establish the current state of research. Renewed fieldwork has made it possible to assemble a solid corpus of data on Capsian occupation and the Neolithisation of human groups. The study also aims to determine responses to local biotopes and environmental variations. Finally, an understanding of Neolithic socio-technical changes and the interpretation of the material remains belonging to the Capsian symbolic sphere is advanced.